Design and Performance Evaluation of a Wet Cell HHO Generator as a Fuel Supplement for a Four-Stroke 125 cc Gasoline Engine - Moh. Ali Sidik; Komarudin Komarudin; Denny Prumanto; Muhammad Iqbal Rasyid Ramadhan; Andi Mamonto (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The increasing use of gasoline-powered motorcycles contributes significantly to fuel consumption and exhaust emissions, particularly carbon monoxide (CO) and hydrocarbons (HC). One approach to improving combustion efficiency is the utilization of oxyhydrogen (HHO) gas as a supplementary fuel. This study aimed to design and evaluate the performance of a wet cell HHO generator as a fuel supplement for a 125 cc four-stroke gasoline engine. The developed system employed an 11-plate Stainless Steel 316L wet cell reactor with a 1.5 mm electrode gap and a 2% potassium hydroxide (KOH) electrolyte solution. The HHO generator was operated at a constant current of 2.5 A. Experimental testing included HHO production rate measurement, chassis dynamometer testing, specific fuel consumption (SFC) evaluation, and exhaust emission analysis under standard and HHO-assisted operating conditions. The functional test results showed that the reactor produced HHO gas at a stable average rate of 43.88 ml/min. Performance testing indicated that HHO supplementation increased average engine torque by 20.39% and average power output by 17.31%. In addition, the average SFC was reduced by 46.5%, indicating improved fuel utilization efficiency. Exhaust emission measurements revealed a reduction in average CO emissions from 2.01% to 0.56% and HC emissions from 376 ppm to 228 ppm. These findings demonstrate that the proposed wet cell HHO generator operated reliably and effectively enhanced engine performance, improved fuel economy, and reduced exhaust emissions in a 125 cc four-stroke gasoline engine.